Effect of AB Mix and Seed Rates on Unhulled Rice Green Fodder Productivity - Tera Fit Rayani; Artiqie Gita Yuardi; Annisa Hakim; Pria Sembada (Jurnal Ilmu Pertanian Indonesia, 2025)
Land scarcity has become a concern in forage production activities, necessitating the development of an alternate hydroponic green fodder approach. The purpose of this study was to determine the impact of AB Mix nutrition and seed density on the growth, productivity, and quality of green fodder derived from rice grain. The study utilized a 2 × 3 factorial Completely Randomized Design with three replications. The factors studied included the use of AB Mix (without and with AB Mix) and seed density (750, 1000, and 1250 g/m2). This study looked at aspects such as growth, productivity, and green fodder quality. Data was evaluated using the ANOVA test for growth and production, as well as the T test for green fodder quality. The results showed that adding AB Mix greatly improved green fodder growth, productivity, and quality. A seed density of 1250 g/m2 produced the highest productivity results. Keywords: AB Mix, green fodder, land scarcity, seed rates